Strategi Kepala Sekolah Mengembangkan Pendidikan Karakter Sesuai Profil Pelajar Pancasila di SD Negeri Kelurahan 15 Ulu Palembang - Rahmatul Jariah Zany (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
Character building needs to be fostered from an early age in order to have a quality character. Actually, everyone has the potential for good character since birth, but this potential must be continuously fostered through coaching and habituation from an early age. This study aims to analyze the principal's strategy in developing character education according to the profile of Pancasila students in elementary schools. The method used in this research is qualitative method. Data collection tools use observation, interview, and documentation methods. Data analysis uses descriptive qualitative with research stages that refer to Miles and Huberman's theory, namely (1) Collecting data, (2) Data reduction, (3) Data presentation, (4) Conclusion drawing. The results stated that the principal's strategy to develop character education has three stages starting from (1) planning, (2) implementation, and (3) evaluation. The principal's strategy to develop character education according to the profile of Pancasila students is in line with the development of student character which is carried out comprehensively and has an impact on the development of students' affective, cognitive, and psychomotor aspects. So character building needs to be fostered from an early age in order to have a quality character.